Mental healthcare among displaced Congolese: policy and stakeholders' analysis - Mutombo, Paulin Beya Wa Bitadi; Lobukulu, Genese Lolimo; Walker, Rebecca (Frontiers in Human Dynamics, 2024)
The Democratic Republic of Congo (DRC) has been the subject of several armed conflicts for more than two decades, causing the displacement of millions of Congolese in and outside the country and impacting on their mental health and wellbeing. Mental healthcare interventions are a vital component for the displaced to holistically integrate into their new communities. This policy brief draws from a systematic review of various laws and policies as well as stakeholders' analysis to address the mental health issues of internally displaced persons (IDPs) in the DRC. In addition, we examine data from 32 interviews with various stakeholders at the national level and in 4 provinces of the DRC (Kasai Central, Tanganyika, South Kivu and Ituri). The findings show that while the DRC has committed to progressive policies and conventions the implementation of these policies and conventions, however, remains insufficient. There are also limited local and international stakeholders that provide forms of psychosocial support to IDPs and, effectively address mental health challenges in context. In addition, the provision of such care is limited by the scarcity of specialized and skilled staffs. These findings point to the need to strengthen mental health system governance. This should include scaling up of the integration of mental healthcare at the operational level, the training of community health workers in the screening of mental health issues and the sensitization of the IDPs and the host population to help them change their perception of mental ill-health.